Ответы и объяснения

Лучший Ответ!
  • Yena
  • главный мозг
2013-03-31T19:42:48+00:00

ctgx(ctgx+1)=0

ctgx=0                                        или                               ctgx+1=0

x=\frac{\pi}{2}+\pi n                                              ctgx=-1

   n=-1                                                                x=\frac{3\pi}{4}+\pi k

x=-\frac{\pi}{2}                                                        k=-1

      n=0                                                              x=-\frac{\pi}{4}  

</span>x=\frac{\pi}{2}<span>                                                                                            k=0

                                                                                        x=\frac{3\pi}{4}         

т.е. на данном промежутке находятся 4 корня